Práticas e nível de conhecimento sobre doença cerebrovascular em um hospital universitário: Parte 2. educação médica na nova era de tratamento do infarto cerebral Knowledge and attitudes regarding stroke in a Brazilian teaching hospital: Part 2. Physicians should be prepared for a new era of stroke treatment - Charles André; Letícia L. Vermelho; Ronir Raggio; Mônica F. Costa; Sérgio A. P. Novis (Arquivos de Neuro-Psiquiatria)
OBJETIVOS: Determinar o nível de conhecimento e a conduta prática dos médicos de um hospital universitário diante do acidente vascular cerebral encefálico (AVE). Contexto: Hospital Universitário. Entrevista direta de amostra de 762 médicos e professores. MÉTODO: Pré-teste para otimização do instrumento e cálculo amostrai. Entrevista de 48 médicos sorteados. Inquérito consistindo em 32 questões sobre fisiopatologia, epidemiologia e mortalidade, clínica, fatores de risco, evolução e tratamento, comportamento pessoal diante da doença. RESULTADOS: Os médicos revelam adequado nível de conhecimento teórico sobre o AVE. Entretanto valorizam excessivamente a presença de cefaléia como indicador da doença, e tendem a subestimar a importância epidemiológica e as possibilidades de intervenção e recuperação após o icto. CONCLUSÕES: A comunidade estudada não parece ter absorvido as mudanças fundamentais de atitude médica diante da doença cerebrovascular. A necessidade de disseminar o conceito do AVE como urgência médica exigirá esforços educacionais específicos em nível de graduação e pós-graduação. BACKGROUND AND PURPOSE: This study was undertaken to evaluate physicians working at a University Hospital as to their knowledge and attitudes towards stroke. METHODS: Individuals working in the hospital were divided in two groups, Health care workers (HCW) and non-Health care workers (NHCW), and further subdivided according to level of schooling, resulting in seven strata. A closed questionnaire addressing epidemiology, risk factors, pathophysiology, typical symptoms, treatment, clinical course and personal attitudes towards smoking and blood pressure control, was applied to a random sample of each stratum (total n = 309). The physicians group included 48 individuals. Kruskal-Wallis test for multiple comparisons of non-parametric data was used. Special attention was given to the wrong answers. RESULTS: Physicians correctly answered 92.6% of the questions. Their performance was superior to that of all other groups in all subgroups of questions. However, a large number of errors was found in questions addressing mortality and hospital mortality following stroke and the intimate relation between coronary and cerebral atherosclerosis. Treatment options in cerebral infarction are also poorly recognised. CONCLUSION: Although physicians general knowledge about stroke is good, they frequently do not perceive it as a critical disease requiring urgent hospital evaluation and care. The importance of a thorough cardiac evaluation following stroke and of the intimate relation between cardiac and cerebral ischemic disease is also unclear to this group. More hours of stroke teaching and practical training in stroke could possibly fill these gaps.